CIRCULARITY IN THE STEEL PACKAGING SECTOR: AN ANALYSIS OF THE MAIN BARRIERS AND OPPORTUNITIES - de Castro, Sebastião Juarez; Rodrigues, Vinícius Picanço; Duarte, André Luis de Castro Moura; Claro, Priscila Borin de Oliveira (Revista Gestão da Produção Operações e Sistemas, 2023)
Abstract Paper aims: Map the life cycle of metal packaging, investigate the barriers and enablers to the adoption of circular practices in the steel packaging sector in Brazil. subject of study: Consist of adoption of a circular model of production and consumption, in which post-consumer raw materials are reintegrated into their respective value chains. Research method: A literature review is combined with qualitative research involving key sector experts to examine how the Brazilian steel packaging sector can transition to a more circular value chain. Main findings: This research indicate that steel packaging has the potential to join a group of products with closed-loop production cycles and that steel can be recycled indefinitely without losing the original properties. Implications for theory and practice: If endless recycling of steel raw materials, there will be no need to mine new ore for new steel packaging.